Reconexões e desconexões terrestres : uma reflexão sobre a frente de modernização em narrativas da crise ecológica e climática - Beatriz Judice Magalhães (2019)
The ecological and climate crisis has been giving rise to reflections by researchers from various fields, from the Earth system sciences to the human and social sciences. In 2016, the International Union of Geological Sciences proposed the official adoption of the Anthropocene as a new geological period. The proposition led to analyzes of various areas, as well as several alternative formulations, such as Capitalocene (as proposed by Jason Moore), Plantationocene (by Donna Haraway and Anna Tsing) and Gaia intrusion (by Isabelle Stengers). In the sphere of action by governments, international organizations and nongovernmental organizations, from the Stockholm conference in 1972 to the adoption of Agenda 2030 in 2015, there are many reference documents formulated within the United Nations as an attempt towards a propositive response to the perceptions of various environmental problems and, from the late 1980s, also of problems related to climate change. Understanding the documents and texts mentioned as two major groups of narratives about the ecological and climate crisis, I seek to reflect on the relationship of these narratives with the front of modernization, defined according to Bruno Latour. In this sense, the approaches of themes such as social and environmental diversity and the suggested configurations among economy, technology, society and environment are of special interest for the intended purpose. The first two chapters cover descriptions and analysis of the narratives. The first presents several approaches to the crisis built on the idea of the geological Anthropocene, either in line with or, to varying degrees, critical of it. The second brings reflections on United Nations (UN) documents focused on the theme of sustainable development, since those related to the first international conferences on relations between human populations and the environment to the Sustainable Development Goals (SDG) agenda adopted in 2015. In the third and last chapter, considerations are made about the (re) lines of conflict drawn from the most recent recognition of the ecological and climate crisis represented by the diffusion of the Anthropocene. It also takes into account the compositions, actions and boundaries of decision-making arenas such as the nation state and multilateral organizations, giving rise to considerations such as representativeness, ontological conflicts and potential disputes related to the current geopolitical configuration, as well as some solutions suggested in the different narratives studied. According to the argument of the thesis, such solutions can be characterized as terrestrial reconnections or disconnections, that is, they point to a transformation of fundamental elements of the modernization front, or, on the contrary, to bring it to the last consequences.